2021
DOI: 10.1097/jsm.0000000000000882
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Insufficiency and Baseline Preseason Concussion-Like Symptom Reporting in Youth Athletes

Abstract: To examine the association between insufficient sleep and baseline symptom reporting in healthy student athletes. Design: Cross-sectional cohort study. Setting: Preseason testing for student athletes. Participants: Student athletes (n 5 19 529) aged 13 to 19 years who completed the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT), including the number of hours slept the night before, and denied having developmental/health conditions, a concussion in the past 6 months, and a previous history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(63 reference statements)
1
1
0
Order By: Relevance
“…Insufficient sleep also was independently related to perceived cognitive impairment ( Table 4 ). This is consistent with prior studies of high school student athletes reporting that insufficient sleep is associated with greater physical, emotional, and cognitive symptoms during baseline preseason health evaluations ( McClure et al, 2014 ; Silverberg et al, 2016 ; Terry et al, 2021 ; Moran and Ingargiola, 2022 ), psychosocial adversities, such as being bullied, having forced sex or being subjected to dating violence in the past year, and feeling unsafe or being threatened at school, were independently associated with perceived cognitive impairment in both boys and girls—even after controlling for the associations with depression and suicidality ( Table 4 ). A lifetime history of using illicit drugs three or more times also was an independent predictor after controlling for depression and suicidality.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Insufficient sleep also was independently related to perceived cognitive impairment ( Table 4 ). This is consistent with prior studies of high school student athletes reporting that insufficient sleep is associated with greater physical, emotional, and cognitive symptoms during baseline preseason health evaluations ( McClure et al, 2014 ; Silverberg et al, 2016 ; Terry et al, 2021 ; Moran and Ingargiola, 2022 ), psychosocial adversities, such as being bullied, having forced sex or being subjected to dating violence in the past year, and feeling unsafe or being threatened at school, were independently associated with perceived cognitive impairment in both boys and girls—even after controlling for the associations with depression and suicidality ( Table 4 ). A lifetime history of using illicit drugs three or more times also was an independent predictor after controlling for depression and suicidality.…”
Section: Discussionsupporting
confidence: 91%
“…We hypothesized that students who reported experiencing adversity (e.g., sexual abuse, sexual assault, and bullying), mental health problems (e.g., depression and suicidality), or drug use would endorse cognitive impairment at greater rates than youth who did not report these psychosocial and mental health problems. Because insufficient sleep has been associated with greater physical, emotional, and cognitive symptoms in high school student athletes ( McClure et al, 2014 ; Silverberg et al, 2016 ; Terry et al, 2021 ; Moran and Ingargiola, 2022 ), we hypothesized that insufficient sleep would be associated with greater endorsement of cognitive impairment. Given that researchers have reported that participation in team sports, and a high level of physical activity, are associated with better self-esteem and greater life satisfaction, and lower risk for psychological distress ( Steptoe and Butler, 1996 ; Sabo et al, 2005 ; Brown et al, 2007 ; Taliaferro et al, 2008 ; Babiss and Gangwisch, 2009 ; Eime et al, 2013 ; Sibold et al, 2015 ; McMahon et al, 2017 ; He et al, 2018 ; Guddal et al, 2019 ), we hypothesized that these variables would be associated with lower rates of endorsing cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%